Bronze Age Lives - Harding, A. F. (2021)
The Bronze Age of Europe is a crucial formative period that underlay the civilisations of Greece and Rome, fundamental to our own modern civilisation. A systematic description of it appeared in 2013, but this work offers a series of personal studies of aspects of the period by one of its best known practitioners. The book is based on the idea that different aspects of the Bronze Age can be studied as a series of "lives": the life of people and peoples, of objects, of places, and of societies. Each of these is taken in turn and a range of aspects presented that offer interesting insights into the period. These are based on recent research (for instance on the genetic history of the Old World) as well as on fundamental earlier studies. In addition, there is a consideration of the history of Bronze Age studies, the "life of the Bronze Age". The book provides a novel approach to the Bronze Age based on the personal interests of a well-known Bronze Age scholar. It offers insights into a period that students of other aspects of the ancient world, as well as Bronze Age specialists and general readers, will find interesting and stimulating.